2006
DOI: 10.1007/s11250-006-4322-7
|View full text |Cite
|
Sign up to set email alerts
|

Responses to tuberculin among Zebu cattle in the transhumance regions of Karamoja and Nakasongola district of Uganda

Abstract: Responses to tuberculin in Zebu cattle of the transhumant pastoral farming system in Karamoja region and Nakasongola district in the north-eastern and mid-central regions in Uganda, respectively, were investigated using a comparative intradermal tuberculin skin test. Of the 1864 cattle tested from 30 large units (superherds) in Karamoja and 7 herds in Nakasongola, a total of 28 animals from 19 herds (51.4%) tested positive. Inter-district tuberculin reactor prevalence variations seemed to be influenced by clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
30
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 21 publications
13
30
1
Order By: Relevance
“…However, and Oloya et al (2006) suggested that sex was a weak risk factor similarly to this study where non-significantly more female than male animals were affected. The chronic nature of bovine TB, low transmissibility of the disease in an extensive/ transhumance system and delayed onset of tuberculin positive response in adult and old animals has been attributed to the long incubation period of the disease, pre-allergenic status, and acquired and maternal immunity (Kazwala et al 2001b;Oloya et al 2006). These factors were also noted as important risk factors in this study.…”
Section: Prevalence Of Bovine Tuberculosis Based On Tuberculin Skin Tsupporting
confidence: 68%
See 4 more Smart Citations
“…However, and Oloya et al (2006) suggested that sex was a weak risk factor similarly to this study where non-significantly more female than male animals were affected. The chronic nature of bovine TB, low transmissibility of the disease in an extensive/ transhumance system and delayed onset of tuberculin positive response in adult and old animals has been attributed to the long incubation period of the disease, pre-allergenic status, and acquired and maternal immunity (Kazwala et al 2001b;Oloya et al 2006). These factors were also noted as important risk factors in this study.…”
Section: Prevalence Of Bovine Tuberculosis Based On Tuberculin Skin Tsupporting
confidence: 68%
“…In this study, animal environments were generally humid or wet and favourable for long survival of TB agents (Goodchild and CliftonHadley 2001;Philips et al 2003). However, contradictory results of lower bovine TB prevalence in cattle maintained in traditional pastoral systems in Uganda and Ethiopia were associated with the relatively dryer conditions of the environments (Oloya et al 2006;Ameni et al 2007;Inangolet et al 2008). Traditional pastoral systems in the tropics that create risks characteristic of intensive farming in relation to the transmission of bovine TB have been well documented (O'Reilly and Daborn 1995;Omer et al 2001;Ayele et al 2004).…”
Section: Prevalence Of Bovine Tuberculosis Based On Tuberculin Skin Tmentioning
confidence: 79%
See 3 more Smart Citations